Olfactory subsystems in mammals: morphology, genetic and evolution - Ignacio Salazar (Frontiers Research Topics, 2015)
The nasal cavity and the elements it comprises are lined by mucosa. This mucosa contains olfactory sensory neurons, which are organized into four different territories: main olfactory epithelium, septal organ, vomeronasal epithelium and ganglion of Grünemberg. From a morphological point of view, these territories could initially be considered as isolated olfactory subsystems, which - as a whole or independently - have been addressed in the contributions enclosed in this Topic.